Risk Factors for Treatment Drop-Out: Implications for Adverse Outcomes When Treating Opioid Use Disorder. Issue 4 (1st October 2020) - Ann Iovine, Patricia; Drachman, David; Kirane, Harshal
ABSTRACT: Pathways to resolve the opioid epidemic focus on enhancing addiction treatment. Dropout rates from outpatient buprenorphine-naloxone (BN) treatment remain as high as 35% to 59%, contributing to poor treatment outcomes. Treatment interventions targeting retention require identification of dropout risk factors. This study used the New York State Office of Alcohol and Substance Abuse Services database to analyze patient information from an ancillary withdrawal management program. Binary logistic regression identified dropout trends. Use of alprazolam or cocaine and age (< 26 years old) correlated with increased likelihood of treatment drop-out. In contrast, a history of domestic violence or intimate partner violence, alcohol use, or prior hospitalization for a psychiatric disorder (hospital stay < 30 days) were associated with an increased likelihood of retention. Potentially modifiable dropout risk factors exist in BN treatment. Recommendations for treatment programs using BN treatment are included.